A Randomized, Double-Blind, Placebo-Controlled Trial Protocol Using the Fuzhengxiaoliu Patch for the Management of Primary Liver Cancer Pain - Li S; Wang B; Deng J; Li H; Wu Y; Fang Y; Yan B; Chen Y (Journal of Pain Research)
Siman Li,1 Binding Wang,1 Jiayao Deng,2 Haiyan Li,2 Yong Wu,3 Yu Fang,2 Bohua Yan,2 Yu Chen2 1School of Clinical Medicine, Chengdu University of TCM, Chengdu, Sichuan, People’s Republic of China; 2Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People’s Republic of China; 3Chengdu Zhongxiang Pharmaceutical Technology Co., Ltd., Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Bohua Yan; Yu Chen, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan, People’s Republic of China, Email yanbohuagcp@163.com; 735405661@qq.comObjective: Chronic pain strongly affects the quality of life of patients with liver cancer pain. Safe and effective management of cancer-related pain is a worldwide challenge. Traditional Chinese medicine (TCM) has rich clinical experience in the treatment of cancer pain. The Fuzhengxiaoliu patch (FZXLP) is a compound TCM with the effects of detoxification and pain relief and has shown great efficacy in the treatment of patients with liver cancer, but high-quality clinical research that provides research-based evidence is lacking. We designed a randomized, double-blind, placebo-controlled trial to explore and evaluate the efficacy of FZXLP for the treatment of liver cancer pain.Methods: This is a prospective, randomized, double-blind, placebo-controlled trial. The trial will enrol 72 participants with primary liver cancer with cancer pain (damp-heat stagnation and toxin and blood stasis syndrome). The primary objective is to measure the reduction in pain using FZXLP in combination with tegafur, gimeracil and oteracil potassium capsule (S-1) compared to the placebo group with S-1. Pain will be measured by the number of opioids used, Chinese versions of the numerical rating scale (NRS), pain relief rate and number of breakthrough cases of cancer pain (BTcP). The secondary objectives include response evaluation criteria in solid tumors (RECIST), tumor markers, TCM syndrome scores, weight, functional assessment of cancer therapy-hepatobiliary (FACT-Hep) questionnaire scores, and self-rating anxiety scale scores. Adverse events (AEs) will be recorded throughout the study.Discussion: This study integrated TCM with clinical research to assess the efficacy and safety of the addition of FZXLP in the treatment of primary liver cancer pain.Trial registration: Chinese clinical trial registry, ChiCTR2300076951, Registered on October 25, 2023. https://www.chictr.org.cn/showproj.html?proj=209608.Keywords: primary liver cancer, traditional Chinese medicine, Chinese herb, cancer pain management, randomized controlled trial